The Disappearence of Presence: On Heidegger’s Paths for a “Magical” Hermeneutics of Medium and Truth - Pisano, Libera (Sens public, 2019)
In this contribution I would like to investigate the conjunction between technology, media, language and aletheia – according to Heidegger’s understanding of this term – , while also shedding light on its connection to magic. Martin Heidegger is the German philosopher who offers the most rigorous reflection on the question of technology. In his famous conference The Question Concerning Technology [Die Frage nach der Technik] given in Munich in November 1953 and published in 1954, Heidegger expounds the famous thesis according to which: “the essence of technology is by no means anything technological”. He draws upon the notion of ἀλήθεια as un-concealment to open up another thinking of technology, according to the idea that it is a way of revealing. Starting from Heidegger’s account of technology, my essay is mainly structured in two parts: the first one concerns the notion of medium in general related to his critique towards the truth as correspondence; the second one examines the account of ἀλήθεια as an alternative conception of truth, namely as un-concealment of reality, in order to show its affinities with magic.